Early-Onset Epileptic Encephalopathy with Phospholipase C Beta 1 Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
The clinical presentation and evolution of epileptic encephalopathy associated with a loss-of-function mutation in the phospholipase C-b 1 gene are reported in a male infant with infantile spasms treated at the University of Birmingham School of Medicine, UK.